Durability of the bond strength of self-adhesive resin cements to human dentin - De Melo, Renata Maraues [UNESP]; Amaral, Regina; Galhano, Graziela [UNESP]; Vanderlei, Aleska; Bottino, Marco Antonio; Valandro, Luiz Felipe (My University, 2009)
This study subjected two self-adhesive resin cements and two conventional resin cements to dry and aging conditions, to compare their microtensile bond strengths (MTBS) to dentin. Using four different luting systems (n = 10), 40 composite resin blocks (each 5x5x4 mm) were cemented to flat human crown dentin surfaces. The specimens were stored in water for 24 hours (37°C), at which point each specimen was sectioned along two axes to obtain beams that were divided randomly into two groups: dry samples, which were tested immediately, and samples that were subjected to accelerated aging conditions (12, 000 thermocycles followed by storage for 150 days). The μTBS results were affected significantly by the luting system used (P < 40001). Only the μTBS of Rely-X Unicem was reduced significantly after aging; the μTBS remained stable or increased for the other self-adhesive resin cement and the two conventional cements.
Keywords: dentin bonding agent; resin cement; dental bonding; dental care; dentin; human; materials testing; tensile strength; time; Dental Bonding; Dental Stress Analysis; Dentin; Dentin-Bonding Agents; Humans; Materials Testing; Resin Cements; Tensile Strength; Time Factors